14-3-3ζ and 14-3-3ε are involved in innate immune responses in Pacific abalone (Haliotis discus hannai). (November 2021) - Xue, Rui; Yang, Dinglong; Han, Yijing; Deng, Qinyou; Wang, Xin; Liu, Xiangquan; Zhao, Jianmin
Abstract: The 14-3-3 proteins play important roles in various cellular processes by binding to different ligands, but little is known about these proteins in mollusks. In this study, two 14-3-3 cDNAs were identified from the Pacific abalone Haliotis discus hannai (designated 14-3-3ζ and 14-3-3ε ), possessing 59.40% identity with each other. Both genes were predominantly expressed in the gills of unchallenged abalones, and their mRNA signals could also be detected in several other tissues, including the mantle, hepatopancreas and ovary. However, after Vibrio harveyi challenge, hemocytes were induced significantly ( p < 0.01). Meanwhile, phagocytosis was inhibited, but apoptosis, reactive oxygen species formation, and caspase 3 expression were significantly induced ( p < 0.01), and they were all suppressed with 14-3-3ζ knockdown ( p < 0.01). The differences were that silencing 14-3-3ε reverted the decline in the phagocytic rate derived from bacterial infection, while ROS formation was not influenced significantly. In addition, the expression levels of several antimicrobial peptide and proinflammatory cytokine genes were also decreased with the silencing of 14-3-3 genes. However, with the knockdown of 14-3-3ζ, the expression of 14-3-3ε was further significantly increased ( p < 0.01), and vice versa. Overall, our results suggested that 14-3-3ζ and 14-3-3ε should play important roles in innate immunity against V. harveyi infection. Highlights: Two abalone 14-3-3 cDNAs were identified . They regulated cellular immunity. They might exist a compensatory relationship.